Extent of implementation of food environment policies by the Malaysian Government: gaps and priority recommendations. Issue 18 (2nd October 2018) - Ng, SeeHoe; Swinburn, Boyd; Kelly, Bridget; Vandevijvere, Stefanie; Yeatman, Heather; Ismail, Mohd Noor; Karupaiah, Tilakavati
Abstract: Objective: To determine the degree of food environment policies that have been implemented and supported by the Malaysian Government, in comparison to international best practice, and to establish prioritised recommendations for the government based on the identified implementation gaps. Design: The Healthy Food-Environment Policy Index (Food-EPI) comprises forty-seven indicators of government policy practice. Local evidence of each indicator was compiled from government institutions and verified by related government stakeholders. The extent of implementation of the policies was rated by experts against international best practices. Rating results were used to identify and propose policy actions which were subsequently prioritised by the experts based on 'importance' and 'achievability' criteria. The policy actions with relatively higher 'achievability' and 'importance' were set as priority recommendations for government action. Setting: Malaysia. Subjects: Twenty-six local experts. Results: Majority (62 %) of indicators was rated 'low' implementation with no indicator rated as either 'high' or 'very little, if any' in terms of implementation. The top five recommendations were (i) restrict unhealthy food marketing in children's settings and (ii) on broadcast media; (iii) mandatory nutrition labelling for added sugars; (iv) designation of priority research areas related to obesity prevention and diet-related non-communicable diseases; and (v) introduce energy labelling on menu boards for fast-food outlets. Conclusions: This first policy study conducted in Malaysia identified a number of gaps in implementation of key policies to promote healthy food environments, compared with international best practices. Study findings could strengthen civil society advocacies for government accountability to create a healthier food environment.